KEKERABATAN MOLEKULER DARI KULTIVAR BUNGA MATAHARI TEDDY BEAR, SKYSCRAPER, LEOM QUEEN DAN BUNGA MATAHARI MENGGUNAKAN MARKA RAPD - Tanudharma, Gabriella Ashari; Sasongko, Nurtjahjo Dwi; Yuniaty, Alice (Fakultas Biologi Universitas Jenderal Soedirman, 2020)
Helianthus or sunflower is a genus of plant comprising about 70 species. Common sunflower and other members of Helianthae are cultivated in temperate regions and some tropical regions as food crops for humans, cattle, poultry, and as ornamental plants. The common sunflower is valuable with respect of economic and ornamental point of view. There are many cultivars of sunflower including teddy bear, skyscraper, and lemon queen. Variation among these cultivars has been studied using molecular techniques and the result were used to develop the phylogeny among them. Random Amplified Polymorphic DNA (RAPD) is one of molecular techniques that were used for this purpose. The purpose of this study was to contruct the phylogeny of three sunflower cultivars and common sunflower based on RAPD markers. The RAPD primers used in this study were OPA-2, OPA-9, OPA-13, OPB-2, OPB-4, OPB5, OPB-7, and OPB-11. Data analysis based on molecular data showed that genetic relationship among Lemon Queen, Skyscraper, Teddy Bear and Common sunflower based on RAPD markers shows that the cultivars studied are grouped into three main groups, namely: Group I Lemon Queen and Skyscraper, Group II Teddy Bear, and Group III Common sunflower; the closest kinship is shown between Lemon Queen and Skyscraper.